Fetal surgery. Issue 6 (15th March 2021) - Sampat, K; Losty, P D
Abstract: Fetal medicine is a super-specialty enterprise and a technology-driven field. The growth and interest in fetal surgery can be largely attributed to advances in fetal imaging and bespoke instruments for in utero intervention. Previously fatal fetal conditions are now being treated using open surgery, minimally invasive procedures, and percutaneous fetal technologies. Several fetal conditions, including myelomeningocele and twin-to-twin transfusion syndrome, have been tested rigorously in RCTs. However, as the specialty of fetal surgery grows, a robust evidence base with long-term follow-up is obligatory for every procedure. This article offers an overview of fetal surgery and antenatal intervention. As more cutting edge therapies come into clinical practice, growing public opinion and medical ethics will play a significant role in the future of this multidisciplinary specialty. Abstract : Fetal surgery is a super-specialty enterprise and a technology-driven field. This state-of-the-art review makes an effort to provide an overview of fetal intervention procedures, citing the evidence base where this exists.